Recovery Attitudes and Recovery Practices Have an Impact on Psychosocial Outreach Interventions in Community Mental Health Care - Khoury, Emmanuelle (Frontiers in Psychiatry, 2019)
The most recent mental health policies implemented in the province of Québec, Canada have emphasized recovery-oriented mental health practice. Part of this impetus has resulted in significant importance placed on the development of community mental health models in the public health system. The forms of community mental health programs have evolved considerably over time in Québec, but are largely inspired by the evidence-based model of Assertive Community Treatment (ACT). However, if mental health policies and programs in Québec are now emphasizing the role of community mental health, it is also clear that actors on the field are implementing the evolving practice paradigms that dominate our mental health policies, such as recovery, participation, citizenship, in a variable way (Author’s own, 2015; MSSS, 2012). This article presents an ethnographic research study conducted in 2014 and aims to contribute to the understanding of how recovery-oriented mental health policies are understood and implemented in Assertive Community Treatment (ACT) team in downtown Montréal. With the aim of developing integrated knowledge on the issue of recovery in mental health and the conditions it presupposes, this research draws on field experiences from various actors, including service users with severe mental health problems, typically with concomitant disorders and complicated by substance use and-or living in a situation of homelessness. Using a critical constructivist approach, the research sought to: a) explore how participants (stakeholders, users, and psychiatrists) achieve their social order; b) understand the meaning of recovery in mental health; c) apprehend the potential of community interventions to connect the individual to the collective. The results indicate that the (over)use of medico-legal tools and the unchanging conception of "madness" represent obstacles to the sustained development of interventions centered on the person, his living conditions and his recovery. Nevertheless, many interactions between service providers and service users indicate the potential for emerging recovery-oriented practice models, particularly when those interactions are based on positive and egalitarian conceptions between stakeholders and users that lead to the development of spaces for the co-construction innovative practice approaches.